Significance of Pirogov`s scientific ideas for modern organization of Public Health - Semenova L.S.; Koryagin U.A. (Medičnì Perspektivi)
This article is about Nikolay Ivanovich Pirogov, a surgeon and anatomist, prominent scientist and educator, founder of field surgery. He was the first to learn field surgery and military administration in practice. He was the first to use famous triage (the wounded were sorted according to the severity of injuries). N.I.Pirogov considered that well organized triage at dressing stations and temporary military hospitals is the main tool to provide proper care and to prevent harmful consequences. He organized training of medical nurses to help the wounded. He also published the work on the problems of pedagogy in which he proposed reforms of education system. The authors of the article have analyzed N.I.Pirogov`s works and showed their significance for modern social medicine and organization of Public Health.